Cultivation of Chlorella sp. in broiler chicken waste media and its metabolite profile by GC-MS analysis - Rizky Izani; Lany Nurhayati; Devy Susanty (Universitas Nusa Bangsa, 2021)
Broiler Chicken Waste (LTAB) contained Nitrogen, Phosphorus and Potassium. LTAB can be used as an alternative medium for the cultivation of Chlorella sp. In this study, Chlorella sp. was cultured in LTAB at various concentrations (2,4,6,8, and 10%). Growth of Chlorella sp. was measured based on optical density values at a wavelength of 680 nm. Biomass was extracted using chloroform. The extract obtained was identified using Gas Chromatography-Mass Spectroscopy (GC-MS). LTAB 2% was the best medium for the growth of Chlorella sp. (amongst other concentrations). The highest growth rate was on the 10th day. Based on the results of KG-MS, chloroform extract of Chlorella sp. cultured on LTAB 2% contained oleic acid, methyl ester and gamma-sitosterol.Keywords: Chlorella sp, Medium, Waste, chromatographyABSTRAKKultivasi Chlorella sp. pada media limbah ayam broiler dan profil metabolitnya dengan analisis GC-MSLimbah Ternak Ayam Broiler (LTAB) mengandung Nitrogen, Fosfor dan Kalium. LTAB dapat dijadikan media alternatif untuk kultivasi Chlorella sp. Pada penelitian ini, Chlorella sp. dikultur pada LTAB pada berbagai konsentrasi (2,4,6,8, dan 10%). Pertumbuhan Chlorella sp. diukur berdasarkan nilai optical density pada panjang gelombang 680 nm. Biomassa diekstrak menggunakan kloroform. Ekstrak yang diperoleh diidentifikasi meggunakan Gas Chromatography-Mass Spectroscopy (GC-MS). LTAB 2% merupakan media terbaik untuk pertumbuhan Chlorella sp. (diantara konsentrasi lainnya). Laju pertumbuhan tertinggi yaitu pada hari ke-10. Berdasarkan hasil KG-MS, ekstrak kloroform Chlorella sp. yang dikultur pada LTAB 2% mengandung senyawa asam oleat, metil ester dan gamma-sitosterol.Kata kunci: Chlorella sp., media, limbah, Kromatografi